Long‐Term Survival of Individuals Born With Congenital Heart Disease: A Systematic Review and Meta‐Analysis. Issue 6 (16th June 2016) - Best, Kate E.; Rankin, Judith
Abstract : Background: Estimates of long‐term survival are required to adequately assess the variety of health and social services required by those with congenital heart disease (CHD) throughout their lives. Methods and Results: Medline, Embase, and Scopus were searched from inception to June 2015 using MeSH headings and keywords. Population‐based studies that ascertained all persons born with CHD within a predefined area and reported survival estimates at ≥5 years were included. Unadjusted survival estimates for each CHD subtype at ages 1 year, 5 years, 10 years, and so forth were extracted. Pooled survival estimates for each age were calculated using meta‐analyses. Metaregression was performed to examine the impact of study period on survival. Of 7840 identified articles, 16 met the inclusion criteria. Among those with CHD, pooled 1‐year survival was 87.0% (95% CI 82.1–91.2), pooled 5‐year survival was 85.4% (95% CI 79.4–90.5), and pooled 10‐year survival was 81.4% (95% CI 73.8–87.9). There was significant heterogeneity of survival estimates among articles ( P <0.001 for 1‐, 5‐, and 10‐year survival). A more recent study period was significantly associated with greater survival at ages 1 year ( P =0.047), 5 years ( P =0.013), and 10 years ( P =0.046). Survival varied by CHD subtype, with 5‐year survival being greatest for those with ventricular septal defect (96.3%, 95% CI 93.7–98.2) and lowest for those with hypoplastic left heart (12.5%, 95% CI 0.0–41.4). Conclusions: Among persons with CHD, the mortality rate is greatest during the first year of life; however, this systematic review and meta‐analysis showed that survival decreases gradually after infancy and into adulthood.